Sistem Kontrol Buka Tutup Atap Stadion Menggunakan Sensor LDR dan Hujan Berbasis IOT - Aditya Pradana, Rio; Abidin, Zainal; Ilmi, Ulul (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2026)
The advancement of modern stadiums encourages the integration of technologies that enhance comfort and protection for both spectators and players, particularly in response to changing weather conditions. This study aims to design and implement an automatic stadium roof control system based on the Internet of Things (IoT) using an ESP32 microcontroller. The system employs an LDR sensor to detect light intensity and a raindrop sensor to detect rainfall. Sensor data are processed by the ESP32, which controls a gearbox motor via an L298N motor driver. The system is integrated with the Blynk application, enabling real-time remote monitoring and control via smartphone. Experimental results show that the LDR sensor produced ADC values of 3763 (dark), 1040 (bright), and 638 (very bright), while the rain sensor responded within one second when exposed to water. The ESP32 pins functioned correctly with 3.3V outputs, the gearbox motor responded well to driver commands, and the Blynk application displayed data in real time without delay. This prototype demonstrates potential application in small- to medium-scale stadiums and can serve as a reference for the development of IoT-based smart sports facility management.